Formation of the Jinchuan ultramafic intrusion and the world's third largest Ni-Cu sulfide deposit: Associated with the -825 Ma south China mantle plume? - Li, X.; Su, L.; Chung, S.; Li, Zheng-Xiang; Liu, Y.; Song, B.; Liu, D. (American Geophysical Union, 2005)
We report here SHRIMP U-Pb geochronological, geochemical, and Nd isotopic data for the Jinchuan ultramafic intrusion (Gansu Province, China), which hosts the world’s third largest magmatic Ni-Cu sulfide deposits. U-Pb baddeleyite analyses yield an age of 812 ± 26 Ma for the ultramafic intrusion. This age is indistinguishable within analytical uncertainties from the U-Pb zircon ages of 827 ± 8 Ma and 828 ± 3 Ma for the sulfide-bearing ultramafic rocks and the dolerite dykes that cut the ultramafic intrusion, respectively. These U-Pb dating results show beyond doubt that the Jinchuan ultramafic intrusion and associated Ni-Cu sulfide deposit were formed at _825 Ma, rather than _1500 Ma as has been widely believed. The ultramafic rocks exhibit large negative eNd(T) values (_8.9 to _12.0) that decrease with increasing La/Sm, suggesting that their parental magmas were derived from a long-term enriched lithospheric mantle and experienced crustal contamination. Mineralogical, petrological, and geochemical data all indicate that the Jinchuan intrusion was generated by melting of the enriched lithospheric mantle heated by an anomalously hot plume. The U-Pb ages of _825 Ma for igneous baddeleyites and zircons and _900–880 Ma for inherited zircons in the Jinchuan mafic-ultramafic rocks are comparable with those in the Qaidam block and Qilian belt, the western extension of the Qinling belt that was likely derived from northern Yangtze craton. The Jinchuan N -Cu sulfide-bearing intrusion, along with coeval regional plumerelated mafic dykes and tholeiites, and mafic-ultramafic complexes with associated V-Ti and Ni-Cu-PGE mineralization, is interpreted to be genetically related to the _825 Ma south China mantle plume.